The strategic use of social identity - Tom Lane (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2023)
The importance of social identities (e.g. race, gender, political ideology) in economic interactions is well established, but little is known about how people strategically manipulate the visibility or salience of their multiple identity types. This paper experimentally explores a common type of situation in which one party can choose between different identity characteristics to truthfully reveal about oneself before entering an economic exchange. Results demonstrate the choice this party makes has substantial potential to influence their payoff: individuals can increase earnings by around 22% by selecting the characteristic most favoured by their counterpart, relative to choosing randomly. Anticipating discriminatory treatment, individuals make strategic choices over which characteristic to reveal, and benefit from a broadly accurate understanding of which dimensions of social identity counterparts will more strongly discriminate along. However, they only reap a fraction of the potential returns from strategic social identity revelation, partly because beliefs about counterparts' likely behaviour are saddled with misperceptions (for instance, overestimating likely in-group favouritism). Approximately half of individuals display willingness to sacrifice expected payoffs in exchange for making their preferred characteristics visible, suggesting that intrinsic utility is derived from social identity.
Keywords: D83; D91; J15; J16; 330; Social Identity; Multidimensionality; Discrimination; Prediction Accuracy; Strategic Revelation